KARAKTERISTIK NAMA DIRI MASYARAKAT TANA AI KABUPATEN SIKKA BERDASARKAN PERSPEKTIF LINGUISTIK KEBUDAYAAN - Patrisius Kami (IdeBahasa, 2023)
For the Tana AI people in Sika Flores Regency, NTT, names are not just names, but names given by parents have philosophical and cultural meanings from each character of the name. Personal name in the form of Nickname or Substitute Name is used to avoid misuse of the original name; third, Personal Name with Clan Name; and Proper Name with Modern Name. From this understanding, this research is a type of qualitative descriptive research, while the theoretical basis for interpreting the characteristics of names is anthroponymy which is explained by (Ziolkowska, 2011) that one of the elements that can be used to identify people is character names. Based on the results of the analysis, there are three characters of names in the Tana Ai community, namely, (1) Names Connect the Past and the Future. For the Tana Ai people, names are not just accessories and signs for each individual to complete personal identity; the Tana Ai people consider the name a representation of the past; (2) The name is a sign, the Tana Ai people's name is related to their lineage, ancestry, hopes, virtues and so on; (3) As part of Creation, the Tana Ai people believe in a great power that is beyond human ability, a power that makes everything more harmonious and orderly, namely the power of creation. This research is a local wisdom in giving proper names to the Tana Ai people, it is hoped that the Tana Ai people can pass them on to generations because proper names are a form of respect for the person who owns the name, as well as a bond that connects the ancestors with all their descendants.